2010
DOI: 10.1088/1742-6596/234/1/012031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of higher borides and inhomogeneity of oxygen distribution on critical current density of undoped and doped magnesium diboride

Abstract: The effect of doping with Ti, Ta, SiC in complex with synthesis temperature on the amount and distribution of structural inhomogeneities in MgB 2 matrix of high-pressuresynthesized-materials (2 GPa) which can influence pining: higher borides (MgB 12 ) and oxygen-enriched Mg-B-O inclusions, was established and a mechanism of doping effect on j c

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 11 publications
(14 reference statements)
0
31
0
Order By: Relevance
“…The method of preparation (pressure-temperature-time conditions) can affect the stoichiometry of MgB x inclusions, their amount and sizes [6]. The MgB x inclusions in the materials prepared at 2 GPa have near MgB 12 stoichiometry, are well crystallized and their nanohardness and Young modulus are higher than that of sapphire [3], [8]. The presence of higher borides in MgB 2 cannot be revealed by traditional X-ray diffraction analysis due to their fine dispersion in the matrix and the large number of atoms in their unit cells of low symmetry resulting in many "reflecting planes", which essentially reduce the intensities of the X-ray reflections as compared to those of MgB 2 having a simple hexagonal unit cell.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The method of preparation (pressure-temperature-time conditions) can affect the stoichiometry of MgB x inclusions, their amount and sizes [6]. The MgB x inclusions in the materials prepared at 2 GPa have near MgB 12 stoichiometry, are well crystallized and their nanohardness and Young modulus are higher than that of sapphire [3], [8]. The presence of higher borides in MgB 2 cannot be revealed by traditional X-ray diffraction analysis due to their fine dispersion in the matrix and the large number of atoms in their unit cells of low symmetry resulting in many "reflecting planes", which essentially reduce the intensities of the X-ray reflections as compared to those of MgB 2 having a simple hexagonal unit cell.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of Ti on the j c increase was explained in [14] by the formation of a "network" of TiB 2 grains, which refines the structure of MgB 2 and by the absorption of impurity H and the formation of more MgB x inclusions in [8]. Analyzing the data in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher magnesium borides with x > 4 are not seen in the x-ray diffraction patterns [5], possibly because their inclusions are dispersed in the structure and have complicated unit cells with many reflection planes (which makes the x-ray reflections of higher borides rather weak, looking like noise on the MgB 2 background). SEM and Auger studies showed some other results that x-ray analysis with Rietveld refinement.…”
Section: Resultsmentioning
confidence: 99%
“…Several previous investigations have shown that MgB 2 -based materials usually contain a high amount of admixed oxygen in their structure, which does not prevent their excellent superconducting performance [4][5][6]. This oxygen enters in Mg(B,O) 2 inclusions, which can be pinning centers in MgB 2 [7].…”
Section: Introductionmentioning
confidence: 99%